La aplicación del entrenamiento en el desarrollo y perfeccionamiento de la técnica del estilo libre y espalda de los nadadores pre juveniles de la selección de Federación Deportiva Provincial de Loja año 2014 - Castillo Salinas, Darwin Geovanny (2015)
This thesis entitled: Implementation of Training Development and Improvement of the technique of Free and Back Swimmers Youth Pre Style Selection Loja Provincial Sports Federation 2014. And their problem is HOW DOES Application Training in the development and refinement of the technique of Free and Back Swimmers Youth Pre Style Selection Loja Provincial Sports Federation ?, the overall objective to determine the influence of the Implementation of Training Development and Improvement of Technical Style Free and Back of the Youth Pre Swimmers Selection of Loja Provincial Sports Federation, the specific objectives are: Determine methodology for improving the technique of free and backstroke strategies; Knowing how to develop exercises that help to perfect the freestyle and backstroke, propose methodological development and refinement of the technique of free and backstroke strategies. The methodology used is descriptive method; Scientific; Deductive Inductive; and Hypothetical Deductive Method. The instruments used were a form of observation. The population was composed of 20 athletes and 2 coaches and for me literature review based on two variables that is sports training, developmental stage, and in the freestyle and backstroke. The results of this research are then given to analyze the data and percentages, and were represented in graphs, where the discussion is that the methodology used by the trainer exercises does not contribute to the improvement and development of free and backstroke. The conclusions say that the application of the methodology used by the coach exercise does not contribute to the improvement and development of free and backstroke. The recommendations coach should improve the methodological strategies to improve the phases of the free and backstroke.